Retaliasi Sebagai Opsi Alat Penegakan Hukum Penyelesaian Sengketa Perdagangan Internasional Akibat Krisis di Badan Banding World Trade Organization - Pramudyawati, Rima Diah (UNES Law Review, 2024)
Member states have expressed dissatisfaction with the absence of an option to appeal against Panel reports due to the crisis faced by the WTO Appellate Body. The paper examines the reasons behind this crisis and explores alternative dispute settlement mechanisms like the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) and retaliation. After reviewing legal sources related to this issue, the paper concludes that retaliation can be used as an alternative method to resolve international trade disputes in situations where the WTO Appellate Body is not operational.